The indigenous presence in Br azil and the conflicts over the demarcation o f the Jaraguá / SP indigenous land (Revista Internacional de Folkcomunicação, 2020)
This article aims to explain about an indigenous trajectory in Brazil and the conflicts involving the right to use indigenous land, going through the impact caused by colonization, on cultural elements, popular communication, cultural hybridization and on the use of land with limited use to the productive activities and physical and cultural reproduction of the peoples, having as central axis the presentation of problems that involve access and recognition of the right to indigenous land, specifically, in the indigenous village of the Jaraguá / SP neighborhood. A survey was carried out through bibliographic surveys and official websites. Understand a property of the land as an original right, that is, that precedes even the same as the laws of the Federative Republic, the right that they are guaranteed, as a form of historical recovery in respect of what this people represents. Indian people; Land demarcation; Jaraguá indigenous land; Guarani Mbya.